Solvation Engineering via Fluorosurfactant Additive Toward Boosted Lithium-Ion Thermoelectrochemical Cells - Xu, Yinghong; Li, Zhiwei; Wu, Langyuan; Dou, Hui; Zhang, Xiaogang (Nano-Micro Letters, 2024)
Lithium-ion thermoelectrochemical cell (LTEC), featuring simultaneous energy conversion and storage, has emerged as promising candidate for low-grade heat harvesting. However, relatively poor thermosensitivity and heat-to-current behavior limit the application of LTECs using LiPF6 electrolyte. Introducing additives into bulk electrolyte is a reasonable strategy to solve such problem by modifying the solvation structure of electrolyte ions. In this work, we develop a dual-salt electrolyte with fluorosurfactant (FS) additive to achieve high thermopower and durability of LTECs during the conversion of low-grade heat into electricity. The addition of FS induces a unique Li+ solvation with the aggregated double anions through a crowded electrolyte environment, resulting in an enhanced mobility kinetics of Li+ as well as boosted thermoelectrochemical performances. By coupling optimized electrolyte with graphite electrode, a high thermopower of 13.8 mV K−1 and a normalized output power density of 3.99 mW m–2 K–2 as well as an outstanding output energy density of 607.96 J m−2 can be obtained. These results demonstrate that the optimization of electrolyte by regulating solvation structure will inject new vitality into the construction of thermoelectrochemical devices with attractive properties. Highlights: 1 Solvation engineering toward dual-salt electrolyte by fluorosurfactant additive is proposed, which implements the stable interface of electrode/electrolyte coupled with fast ion thermodiffusion, improving the durability and capability of lithium-ion thermoelectrochemical cell. 2 By combining the optimized electrolyte with functional electrodes, as-constructed device exhibits high Seebeck coefficient and energy density based on hybrid mechanisms, which can be extended as self-power supply for smart electronics.